Sociometric Status in Bullying Perpetrators: A Systematic Review - Cañas, Elizabeth; Estevez, Estefania; Estevez, Jesus F. (Frontiers in Communication, 2022)
Numerous studies have analyzed the relationship between sociometric status and bullying but it is difficult to reach a consensus regarding this issue. Objective: The present study carried out a systematic review on the sociometric status of adolescent bullies. Design: The bibliographic search was carried out in the PsichInfo, Scopus, PubMed, and Web of Science databases. A total of 29 studies published between 2001 and 2021 were selected by meeting the inclusion criteria. Results: The findings of the consulted studies defend three positions. First, bullying is associated with the popular status in their peer group. Second, rejected or unpopular adolescents tend to perpetrate bullying as a response to the frustration generated by their status. Finally, other group the perpetrators of bullying is set in the middle of these two poles. Conclusions: These results underscore the need to consider the students' sociometric status for designing bullying prevention and intervention programs at school.